NEOTECTONIC FAULTING OF THE NICOYA PENINSULA AND ITS RELATION WITH THE TECTONIC ESCAPE OF THE CENTRAL AMERICAN FOREARC SLIVER - Montero, Walter (2011)
A neotectonic array of faults has been determined in the Nicoya peninsula. In the central and NW sec- tors of the peninsula, blocks restricted by N-S trending dextral slip faults predominates. ENE sinistral slip faults and E-W oblique sinistral-reverse and NW pure reverse faults are confined to the dextral fault blocks. The previous spatial relationships between the different faults are explained by the north translation of this sector of the peninsula and the transrotation occurring inside the blocks. Sinistral and dextral slip faults with apparent similar relevance, and subordi- nate reverse faults have been mapped in the southern Nicoya peninsula. N and less probably E translational movements are inferred in this sector. The neotectonic faulting of the Nicoya peninsula is associated with the Cocos Ridge collision with the central and southern Costa Rica convergent margin, causing the tectonic escape to the NW of the Central American forearc sliver, parallel to the Middle America trench.